2020
DOI: 10.1111/codi.15366
|View full text |Cite
|
Sign up to set email alerts
|

Hartmann's procedure versus intersphincteric abdominoperineal excision (HiP Study): a multicentre prospective cohort study

Abstract: Aim In patients with low rectal cancer it is occasionally necessary to avoid a low coloanal anastomosis due to patient frailty or poor function. In such situations there are two alternative approaches: Hartmann's procedure (HP) or intersphincteric abdominoperineal excision (IAPE). There are few data to guide surgeons as to which of these two procedures is the safest. The aim of this study was to determine the surgical complication rates associated with each procedure. Method This was a multicentre, nonrandomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…The LH group had a higher proportion of ASA Class 3-4 patients at 38-67%, as compared to 17-48% in the ISAPR group. Five studies [7][8][9]12,13 reported on tumour staging, with similar percentages of Stage IIIa or Dukes C stages noted in the LH (50%) and ISAPR (47.6%) groups (Table 3).…”
Section: Patient Characteristicsmentioning
confidence: 80%
See 2 more Smart Citations
“…The LH group had a higher proportion of ASA Class 3-4 patients at 38-67%, as compared to 17-48% in the ISAPR group. Five studies [7][8][9]12,13 reported on tumour staging, with similar percentages of Stage IIIa or Dukes C stages noted in the LH (50%) and ISAPR (47.6%) groups (Table 3).…”
Section: Patient Characteristicsmentioning
confidence: 80%
“…After screening for full text reviews, a total of 12 studies were included in the study. The majority of papers 1,2,6,[8][9][10][11] have only elective patients in their inclusion criteria. Some papers have intentionally excluded emergency cases.…”
Section: Search Results and Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The increasing incidence of rectal cancer, especially among older people, compels surgeons to reconsider the treatment for rectal cancer [1,2]. The role of HP as a treatment option for rectal cancer has long been debated and its use varies widely between countries [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…I read with great interest the excellent study by Hayley Fowler and colleagues and led by Dale Vimalachandran entitled ‘Hartmann's procedure versus intersphincteric abdominoperineal excision (HiP Study): a multicentre prospective cohort study’ [1]. This is a relevant topic of clinical interest to the colorectal community.…”
mentioning
confidence: 99%